Motivations for sustainability reporting a case study in a textile company - Pires, Amélia M.M. (2023)
The disclosure of information within the scope of corporate sustainability is particularly directed towards companies of public interest, a reason that is particularly pointed out for the low adherence rate and for considering that reporting practices within this scope are mostly voluntary. On the other hand, there are also those who argue that larger companies and those operating in activity sectors that are more sensitive to environmental and social issues tend to show greater awareness and concern for future generations. It is within this scope that this research is developed, although particularly directed towards answering the following question: what leads companies to disclose in the scope of sustainability and how do they do it? To answer this question, the research comprises a literature review and a case study, developed in a company of the textile sector. It was possible to conclude that, globally, there is a greater tendency to disclose in companies that are bigger and/or belong to activity sectors that are more sensitive to social and environmental issues. The results also allow presenting the textile industry as a paradigmatic example around sustainable development and reinforce the thesis that the activity sector presents itself as a motivational element to disclose in this context, regardless of size.